1996
DOI: 10.1046/j.1365-2567.1996.451513.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of cytokine receptors on human Langerhans' cells. Changes observed after short‐term culture

Abstract: SUMMARYIt is well established that granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-1 and tumour necrosis factor-a (TNF-a) are involved in Langerhans' cell (LC) development and dendritic cell traffic. However, little is known about the pattern of cytokine receptors on human LC and their modulation during different stages of maturation. The expression of cytokine receptors was studied by flow cytometry on both freshly isolated LC (fLC) and 72-hr cultured LC (cLC). Epidermal cell suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…It is well known that IL-1, TNF-a and C5a are all generated during the early phases of an inflammatory response and that epidermal rLC express IL-1R and 75 kD TNFR. 41 In this scene the upregulation of the C5aR on LC might be one of the components that might trigger LC migration and the subsequent adaptative immunity during an inflammatory process, as recently postulated by Katz and co-workers. 42 …”
Section: Discussionmentioning
confidence: 84%
“…It is well known that IL-1, TNF-a and C5a are all generated during the early phases of an inflammatory response and that epidermal rLC express IL-1R and 75 kD TNFR. 41 In this scene the upregulation of the C5aR on LC might be one of the components that might trigger LC migration and the subsequent adaptative immunity during an inflammatory process, as recently postulated by Katz and co-workers. 42 …”
Section: Discussionmentioning
confidence: 84%
“…It is generally accepted that induction of a cell-mediated immune response to papillomavirus occurs by cross-presentation of papillomavirus antigen by Langerhans cells (LCs), professional antigen-presenting cells (APCs) within the epidermis (44). LCs and dermal dendritic cells, the other professional APCs in the skin, are both derived from the myeloid lineage and express a functional ␥c subunit (31,32). A recent report has suggested that Toll-like receptor signaling through APCs may be an important component in the immune response to papillomavirus infection (56).…”
Section: Discussionmentioning
confidence: 99%
“…39 Single cell suspensions were cultured for 24 h in complete medium. For CTL cytokine secretion assays, only heat-inactivated human AB serum was used throughout the procedure.…”
Section: Preparation Of Epidermal Cell Suspensionsmentioning
confidence: 99%